PENERAPAN MEDIA CUPLIKAN FILM BERBANTUAN PINDAI KODE QR DALAM PEMBELAJARAN TEKS BIOGRAFI - Yani Septiani; Jamjam Sapaat (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2019)
This research is motivated by the lack of varied use of instructional media that influences the learning outcomes and the high-level thinking of student. The purpose of this research is to determine the effectiveness of film footage with QR-code application in understanding biographical text in SMKN 1 Simpang Rimba, South Bangka. The underlying theory is the theory of learning approaches and instructional media related to Higher Order Thinking Skill (HOTS). This research method uses One-Shot Case Study. The research data in the form of pretest and posttest data is understanding biographical text in formative test with HOTS questions and questionnaire. The result of research is the recognition of film footage with QR code more effective in learning to understand biographical text and it can help students to think higher or to think critically